BZLF1 Expression of EBV is correlated with PARP1 Regulation on Nasopharyngeal Carcinoma Tissues - wahyu nur laili fajri; Ahmad Rofi'i; Fatchiyah Fatchiyah (Journal of Tropical Life Science, 2013)
Nasopharyngeal carcinomas (NPC) is a cancer that arises in the epithelial tissue that covers the inside of the nasopharyngeal mucosa and nasopharynx. Infected Epstein Barr Virus (EBV) cell in a latent infection associated with the expression of nine latent proteins. Latent Membrane Protein 1 (LMP1) is one of latent proteins, and mayor EBV oncoprotein, with functions including virus growth, and to activate BamHI-Z Leftward Reading Frame 1 (BZLF1)-EBV, which can inhibit p53 to induce apoptotic resistance, metastasis, and immune modulation. The body will respond to the expansion of EBV infection with activation of Poly(ADP-ribose)Polymerase-1 (PARP1). The objective of study is to observe the expression of BZLF1 and determine PARP1 regulation in nasopharyngeal tissues. NPC-T2, NPC-T3 and polyp tissues slides are from Ulin Hospital, Banjarmasin. To characterize the necrotic cells such as pyknosis, karyorrhexsis, and karyolysis, histological slides were stained by HE that the necrotic cells measured by using a BX-53 microscope (Olympus) with CellSens Standard software. Tissues slides were stained by using immunofluorohistochemistry with EBV-BZLF1 antibody-Mouse anti-EBV monoclonal antibody against Goat anti-mouse IgG-FITC and anti-PARP1 antibody (MC-10) against Goat anti-mouse IgG labeled Rhodamin. The expression intensities were measured by Confocal Laser Scanning Microscope (Olympus). The percentage number of necrotic cells and BZLF1 and PARP1 expression intensity were analyzed using SPSS 16.0 by one-way ANOVA test with Î± = 0.05, beside that we use correlate and regression analyze. The research showed that the amount of karryorhexis higher than pyknosis and karyolysis in both tissues. BZLF1 expression 1.79 INT/sel (in polyp), 2.76 INT/sel (NPC Type 2) and 4.36 INT/sel (NPC Type 3), PARP1 expression 2.25 INT/sel (in polyp), 3.31 INT/sel (NPC Type 2), dan 5.93 INT/sel (NPC Type 3).The high of intensity of expression BZLF1 induced the increasing of PARP1 expression, but not correlated with percentage of necrotic cell. Interestingly, in all tissues (NPC-T1, NPC-T2 and polyp) is increased number of karyolysis cells properly, but not in pyknosis and karryorrhexis cells. The conclusion of this study indicated that the BZLF1 induce PARP1 to repair DNA damage against EBV infection.Keywords: BZLF1, CLSM, EBV, nasopharyngeal carcinoma, PARP1.